Rhubarb Protect Against Tubulointerstitial Fibrosis by Inhibiting TGF-β/Smad Pathway and Improving Abnormal Metabolome in Chronic Kidney Disease - Zhang, Zhi-Hao; Li, Ming-Hua; Liu, Dan; Chen, Hua; Chen, Dan-Qian; Tan, Ning-Hua; Ma, Shuang-Cheng; Zhao, Ying-Yong (Frontiers in Pharmacology, 2018)
Tubulointerstitial fibrosis is the final common pathway for all kidney diseases leading to chronic kidney disease (CKD). TGF-β/Smad signaling pathway plays a key role in renal fibrosis. Previous studies have revealed that rhubarb extracts attenuated the increase of transforming growth factor-β 1 (TGF-β1) in CKD rats. To gain an in-depth insight into the mechanism of the anti-fibrotic activities of the rhubarb extracts, we investigated the influence of rhubarb extracts on TGF-β/Smad signaling pathway and the influence on metabolome in a rat model of CKD with adenine-induced chronic tubulointerstitial nephropathy. Male Sprague-Dawley rats were divided into four groups, including control, CKD, CKD + petroleum ether extract, CKD + ethyl acetate extract, and CKD + n-butanol extract groups. Kidneys harvested on the week three were evaluated for renal fibrosis, the expression of proteins in TGF-β/Smad signaling pathway and metabolomic study. We found rhubarb extracts suppressed TGF-β/Smad3-mediated renal fibrosis by reducing the TGF-β1, transforming growth factor-β receptor I (TGF-β RI), transforming growth factor-β receptor II (TGF-β RII), Smad2, p-Smad2, Smad3, p-Smad3, and Smad4, meanwhile increased Smad7. In addition, rhubarb extracts mitigated renal injury and dysfunction, and either fully or partially reversed the abnormalities of tissue metabolites. Thus, rebalancing the disorder of TGF-β/Smad signaling and metabolic dysfunction by treatment with rhubarb extracts may represent as an effective therapy for CKD associated with fibrosis.